1987
DOI: 10.1258/002367787780740743
|View full text |Cite
|
Sign up to set email alerts
|

The attachment of filamentous segmented micro-organisms to the distal ileum wall of the mouse: a scanning and transmission electron microscopy study

Abstract: SummaryScanning electron micrographs are presented of the ileal epithelium of mice aged 5, 15, 20 and 25 days. During this period the villous pattern develops to full maturity. By the twentieth day of life a segmented filamentous microorganism colonizes the ileal epithelium and is firmly attached via a small segment. During the first days of colonization the segmented filamentous micro-organisms themselves are subcolonized by small rod-shaped bacteria, presumably lactobacilli. At the age of 25 days this subcol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 16 publications
5
29
0
Order By: Relevance
“…SFB were present exclusively in the feces of children under 3 years of age, showing peak numbers in children between 7 and 12 months of age (Table 1). The agedependent colonization of SFB in humans is consistent with patterns observed in other animal species, such as mice, rats and chickens (Koopman et al, 1987;Davis and Savage, 1974;Blumershine and Savage, 1978). The age-dependent patterns of SFB colonization in humans could be ascribed to the maturation of the host immune system over time.…”
Section: Discussionsupporting
confidence: 79%
“…SFB were present exclusively in the feces of children under 3 years of age, showing peak numbers in children between 7 and 12 months of age (Table 1). The agedependent colonization of SFB in humans is consistent with patterns observed in other animal species, such as mice, rats and chickens (Koopman et al, 1987;Davis and Savage, 1974;Blumershine and Savage, 1978). The age-dependent patterns of SFB colonization in humans could be ascribed to the maturation of the host immune system over time.…”
Section: Discussionsupporting
confidence: 79%
“…They were either scid/ϩ or scid/scid and were born either to F 1 scid/ϩ mothers or to scid/scid mothers. Observations were made on days 13,16,20,24,28,32,36,44,54, and 70 after the birth of the F 2 mice. At each time point, three to five pups from each group were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that SFB were absent during the suckling period and appeared in high numbers shortly after weaning (6,16,28), then dramatically decreased in the small intestine (11). By inoculating 4-week-old GF mice with SFB, Snel et al found a similar decline in SFB occurring in the small intestine within the following weeks, while SFB remained constantly present in the cecum and the number of IgA-secreting cells concomitantly increased in the lamina propria of the small intestine (34).…”
mentioning
confidence: 99%
“…Intestinal colonization by SFB is influenced by various factors, including diet, weaning, strain, housing, and the immune status of both the mother and the host (10,12,13,15,16). SFB attach apically to epithelial cells, with only minor disruption of microvilli and localized actin polymerization at the attachment site (4,9,20 SFB are suggested to function as an important microbial component of the gastrointestinal ecosystem (4).…”
mentioning
confidence: 99%